A new strategy for the treatment of advanced ovarian cancer: utilizing nanotechnology to regulate the tumor microenvironment - Xiong, Zixuan; Huang, Yichun; Cao, Shulong; Huang, Xuqun; Zhang, Haiyuan (Frontiers in Immunology, 2025)
Advanced ovarian cancer (AOC) is prone to recurrence, which can be attributed to drug resistance. Drug resistance may be related to the tumor microenvironment (TME), including the immune and non-immune TME. In the immune TME, the immune effector cells such as dendritic cells (DCs), M1-like tumor-associated macrophages (M1-TAMs), and T cells are inhibited. In contrast, immunosuppressive cells such as M2-like tumor-associated macrophages (M2-TAMs), myeloid-derived suppressor cells (MDSCs), and regulatory T cells (Tregs) are activated. These changes make it difficult to produce immune effects and affect the efficacy of chemo-immunotherapy. In the non-immune TME, mechanisms such as apoptosis inhibition, DNA damage response (DDR), and epithelial-mesenchymal transition (EMT) can promote tumor growth, metastasis, and drug resistance. Despite the challenges posed by the TME in the treatment of AOC, the unique biological advantages of nanoparticles (NPs) make it possible to regulate the TME. NPs can stimulate the immune responses of M1-TAMs, DCs, and T cells while reducing the infiltration of immune suppressive cells such as M2-TAMs and Tregs, thereby regulating the AOC immune TME. In addition, NPs can regulate the non-immune TME by reducing apoptosis in AOC cells, inhibiting homologous recombination (HR) repair, reversing EMT, and achieving the effect of reversing drug resistance. In summary, the application of NPs provides some new venues for clinical treatment in AOC.